2014
DOI: 10.3109/08880018.2014.930767
|View full text |Cite
|
Sign up to set email alerts
|

Wilms’ Tumor: A 24-year Retrospective Study from a Single Center

Abstract: Medical records of 71 children with Wilms' tumor at Sisli Etfal Education and Research Hospital between 1990 and 2014 were reviewed. Mean age at diagnosis was 3.11 years (2 days-7 years). Male to female ratio was M/F = 6/10. The incidence of associated anomaly was 16.9%. Clinical manifestations included abdominal mass (89%), hematuria (30%), hypertansion (25%), abdominal pain (15%), fever (5%), restlessness (2%), weight loss (2%), varicocele (1%). Ultrasound (USG) was the most often initial study in a child pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
2
7
0
14
Order By: Relevance
“…They reported that the prevalence of varicoceles was < 1% in boys aged 2–10. In the child less than 9 years of age, where acute varicoceles are normally not seen, a renal or retroperitoneal tumour is a possibility and should be excluded [ 165 ].…”
Section: Systematic Review To Address Question 14mentioning
confidence: 99%
“…They reported that the prevalence of varicoceles was < 1% in boys aged 2–10. In the child less than 9 years of age, where acute varicoceles are normally not seen, a renal or retroperitoneal tumour is a possibility and should be excluded [ 165 ].…”
Section: Systematic Review To Address Question 14mentioning
confidence: 99%
“…Varicocele is an unusual presentation (~1%) of Wilms' tumor. 5 Angioinvasion of the tumor into renal vein and inferior vena cava results in venous engorgement of spermatic veins resulting in varicocele. Left spermatic vein, unlike right spermatic vein, drains perpendicularly into the renal vein and is more prone for compression because of any mass lesion arising from kidney explaining the common presentation on the left side.…”
Section: Varicocele With An Abdominal Massmentioning
confidence: 99%
“…Нефробластома (опухоль Вильмса) -одна из наиболее часто встречающихся злокачественных эмбриональных опухолей у детей. С точки зрения эмбриогенеза нефробластома представляет собой солидную злокачественную опухоль, состоящую из производных нефрогенной ткани на разной степени дифференцировки [1].…”
Section: Introductionunclassified
“…Обычно опухоль Вильмса возникает спорадически, в 2 % наблюдений она имеет семейный характер, в 10 % случаев она развивается у детей с пороками развития (чаще мочеполовой системы) или генетическими синдромами. Частота встречаемости заболевания среди девочек и мальчиков одинакова [1].…”
Section: Introductionunclassified